Great maps - Brotton, Jerry (London : Dorling Kindersley Limited, 2015)
Traces human development and culture through cartography, from early rock carvings to the latest geospatial technology
Classical maps 1500 BCE-1300 CE -- Discovery and travel 1300-1570 -- New directions and beliefs 1570-1750 -- Thematic maps 1750-1900 -- Modern mapping 1900 to present
Includes index
Keywords: Cartography -- History; Cartography; Maps